Review of the Roles and Interaction of Androgen and Inflammation in Benign Prostatic Hyperplasia - Yu Tong; Ren-yuan Zhou (Mediators of Inflammation)
The lower urinary tract symptoms (LUTSs) and acute urinary retention (AUR) caused by benign prostatic hyperplasia (BPH) can seriously affect the quality of life of elderly men. Studies suggest that both androgens and inflammation greatly influence the occurrence and development of BPH in most patients. These two factors combined can also affect each other, leading to pathological changes in the stromal and epithelial tissue of the prostate transition zone in BPH patients. DHT in the prostate tissue of BPH patients may activate a chronic inflammatory response in the prostate, amplifying the expression of inflammatory factors and upregulating the proliferation ability of prostate tissue.